Interactive governance advancing the paradigm - Torfing, Jacob (Oxford Oxford University Press, 2012)
Governance has become one of the most commonly used concepts in contemporary political science. It is, however, often used to mean a variety of different things. This text helps to clarify this conceptual muddle by concentrating on one variety of governance-interactive governance.
Keywords: Government accountability; Political science; Power (Social sciences)